2018
DOI: 10.1002/jlb.3a0317-106rrr
|View full text |Cite
|
Sign up to set email alerts
|

Induction of endoplasmic reticulum stress under endotoxin tolerance increases inflammatory responses and decreases Pseudomonas aeruginosa pneumonia

Abstract: Endotoxin tolerance develops in the late phase of sepsis to protect cells from an early hyperinflammatory response. Nonetheless, because it induces an immunosuppressive environment, patients with sepsis in its late phase are affected by secondary infections, particularly bacterial pneumonia. Here, we showed that induction of endoplasmic reticulum (ER) stress leads to activation of glycogen synthase kinase 3β (GSK-3β) and X-box-binding protein 1 (XBP-1) in an inositol-requiring enzyme 1α (IRE1α)-mediated manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…NOD1 (but not NOD2) restricts C. jejuni infection in intestinal epithelial cells (90) and therefore may be involved in ER stress-mediated restriction of C. jejuni infection. Other bacteria that induce ER stress and are also inhibited by NOD1 or NOD2 include P. aeruginosa (141)(142)(143)(144)(145), Staphylococcus aureus (146,147), S. Typhimurium (148), and S. pneumoniae (149). Additional studies are necessary to determine a link between bacterium-induced ER stress and NOD1/2 antibacterial effects.…”
Section: Pathogen-induced Er Stress Sensing and Nod1/2mentioning
confidence: 99%
“…NOD1 (but not NOD2) restricts C. jejuni infection in intestinal epithelial cells (90) and therefore may be involved in ER stress-mediated restriction of C. jejuni infection. Other bacteria that induce ER stress and are also inhibited by NOD1 or NOD2 include P. aeruginosa (141)(142)(143)(144)(145), Staphylococcus aureus (146,147), S. Typhimurium (148), and S. pneumoniae (149). Additional studies are necessary to determine a link between bacterium-induced ER stress and NOD1/2 antibacterial effects.…”
Section: Pathogen-induced Er Stress Sensing and Nod1/2mentioning
confidence: 99%
“…ER stress is also involved in the inflammatory response by activating GSK-3β 38 . Activation of ER stress leads to activation of GSK-3β, which in turn restores the inflammatory response in endotoxin-tolerant macrophages 39 . ER stress participated in myocardial ischemia-reperfusion injury by activating GSK-3β 40 , and inhibiting the appeal process can play a role in myocardial protection.…”
Section: Discussionmentioning
confidence: 99%
“…fumigatus antigens, respectively, and it has recently been suggested that ABPA-related symptoms may be attributed to the A. fumigatus-induced ER stress. , P. aeruginosa secretes virulence factors including PCN and TpIE that are known to induce ER stress and activate UPR via the p38 mitogen-activated protein kinase (MAPK) pathway. ,, The relative abundance of multiple proteins associated with protein processing in the ER was increased in the A.…”
Section: Discussionmentioning
confidence: 99%
“…62 In vivo and in vitro studies have demonstrated an increase in ER stress markers in murine lungs and tracheal epithelial cells challenged with A. fumigatus antigens, respectively, and it has recently been suggested that ABPA-related symptoms may be attributed to the A. fumigatus-induced ER stress. 63,64 P. aeruginosa secretes virulence factors including PCN and TpIE that are known to induce ER stress and activate UPR via the p38 mitogen-activated protein kinase (MAPK) pathway. 61,65,66 The relative abundance of multiple proteins associated with protein processing in the ER was increased in the A. fumigatus-and P. aeruginosa-exposed groups compared to that in the controls and sequentially exposed A549 cells.…”
Section: Journal Of Proteome Researchmentioning
confidence: 99%